ON THE OCCURRENCE OF PRIMITIVE ORBITOIDES SPECIES IN GAVROVO – TRIPOLITZA PLATFORM (MAINALON MOUNTAIN, PELOPONNESUS, GREECE) - Zambetakis-Lekkas, A. (Bulletin of the Geological Society of Greece, 2010)
Orbitoides genus is considered as a cosmopolitan one, with a worldwide distribution. It characterizes the open shelf sedimentation of late Cretaceous. Therefore, primitive species of the genus have not the same large paleogeographic distribution as the more evolved species. While evolved species of Orbitoides genus are frequently referred in Hellenids, primitive species are reported for the first time in Mainalon Mountain in central Peloponnessus (Zambetakis-Lekkas & Alexopoulos 2007). In this paper primitive Orbitoides species in the above area are studied and discussed. A new species seems to be identified.